Паровые турбины ОАО "Турбоатом" для тепловых электростанций - Субботин, В. Г.; Левченко, Евгений Владимирович; Швецов, В. Л. (НТУ "ХПИ", 2009)
There are presented the stages of the JSC «Turboatom» progress during the manufacture of the new series turbines and modernization and repair of the turbine-generator sets produced earlier. The mentioned refurbishing and repair allow sustaining the effectiveness, reliability and maneuverability of the Kharkov turbine plants up to the best world samples. There are considered the turbine types manufactured by the works, there are described the structural and operating features.
Keywords: турбогенераторные заводы; турбины противодавленческие; паротурбостроение стационарное; обеспечение качества